Contralateral axillary sentinel lymph node in breast cancer recurrence. Issue 7 (14th April 2020) - Cairns, Cassandra; Greenwalt, Ian; Fan, Kenneth L.; Willey, Shawna C.
Abstract: The rare but significant reports of aberrant lymph node drainage outside of the ipsilateral axilla in patients with breast cancer necessitate a review of the staging and treatment strategies for these patients. Current staging modalities continue to describe this phenomenon as a stage IV cancer, which could have profound implications for clinical management. We report a case of a patient with recurrent right breast invasive ductal carcinoma whose preoperative lymphoscintigraphy revealed sentinel lymph node drainage to the contralateral axilla. This discovery subsequently altered surgical planning and her ultimate stage.